2014
DOI: 10.1177/1933719114532840
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Low-Dose Contraceptive Patch on Efficacy, Bleeding Pattern, and Safety: A 1-Year, Multicenter, Open-Label, Uncontrolled Study

Abstract: This Phase III, uncontrolled, open-label, multicenter study was conducted to investigate the contraceptive efficacy, bleeding pattern, and cycle control of a novel once-a-week contraceptive patch, delivering low-dose ethinyl estradiol (EE) and gestodene (GSD) at the same systemic exposure seen after oral administration of a combined oral contraceptive containing 0.02 mg EE/0.06 mg GSD. Participants were women aged 18 to 35 years, all of whom received the EE/GSD patch for 13 cycles each of 21 treatment days (on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…The findings reported here are in line with those of a phase III study of the contraceptive efficacy of the EE/GSD patch, which found that the Kaplan-Meier probability of contraceptive protection after 364 treatment days was 98.8% and the adjusted Pearl Index was 0.81 [19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings reported here are in line with those of a phase III study of the contraceptive efficacy of the EE/GSD patch, which found that the Kaplan-Meier probability of contraceptive protection after 364 treatment days was 98.8% and the adjusted Pearl Index was 0.81 [19].…”
Section: Discussionsupporting
confidence: 91%
“…3 The tolerability of the two patches was otherwise similar. In terms of study limitations, small sample size restricts the extent to which the data can be used to evaluate pregnancy and safety outcomes; although, the aforementioned phase III study provides reassuring data on pregnancy outcomes, as assessed in a larger number of women (n= 1,631) [19]. Despite this, the risk of rare but pertinent events such as venous thromboembolism cannot reasonably be assessed here.…”
Section: Discussionmentioning
confidence: 95%
“…In terms of study limitations, the small sample size restricts the extent to which the data can be used to evaluate pregnancy and safety outcomes; however, data from a previous phase III study (n= 1,631) of the EE/GSD patch suggest good contraceptive efficacy, with an adjusted Pearl Index score of 0.81 [19]. Despite this, the risk of rare but pertinent events such as venous thromboembolism cannot reasonably be assessed here.…”
Section: Discussionmentioning
confidence: 84%
“…In a larger phase 3 study of the ethinyl estradiol/ gestodene patch (n ¼ 1631), this percentage was slightly lower, with only 5.7% of patches becoming completely detached. 38 In a pooled analysis of data with a norelgestromin/ethinyl estradiol patch (n ¼ 3319), 1.8% of patches were replaced because of complete detachment. 39 In general, the safety profile of the ethinyl estradiol/ gestodene patch was comparable with that observed with other transdermal contraceptive patches.…”
Section: Discussionmentioning
confidence: 99%